Cover Image, Volume 74, Issue 2. Issue 2 (4th March 2017) - Batsir, Sarit; Geiger, Benjamin; Kam, Zvi
Abstract : The cover image, by Benjamin Geiger et al., is based on the Research Article Dynamics of the sealing zone in cultured osteoclasts, DOI:10.1002/cm.21350 .